PROCEDURAL DOCUMENT: STRUCTURING FEATURES (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the role of speech culture in the future professional activities of a lawyer. In particular, it pays attention to the issues of structuring the text of legal content: resolutions and protocols, reveals linguistic features in connection with parts of documents.